2004
DOI: 10.1653/0015-4040(2004)087[0440:badott]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Behavior and Distribution of the Two Fall Armyworm Host Strains in Florida

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
62
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(65 citation statements)
references
References 33 publications
2
62
1
Order By: Relevance
“…Golden Queen, a commercially grown sweet corn variety that, like other sweet corn varieties, is frequently attacked by FAW in Florida (Foster, 1989;Nagoshi and Meagher, 2004). Maize seeds were planted in professional growers mix potting soil (Piedmont Pacific, GA, USA) in 4-in.…”
Section: Plantsmentioning
confidence: 99%
“…Golden Queen, a commercially grown sweet corn variety that, like other sweet corn varieties, is frequently attacked by FAW in Florida (Foster, 1989;Nagoshi and Meagher, 2004). Maize seeds were planted in professional growers mix potting soil (Piedmont Pacific, GA, USA) in 4-in.…”
Section: Plantsmentioning
confidence: 99%
“…These markers included several allozyme electrophoretic variants and DNA polymorphisms, which still remain the only reliable means of discriminating between the morphologically indistinguishable strains (Lu et al 1992, Lu and Adang 1996, McMichael and Prowell 1999, Levy et al 2002, Prowell et al 2004). Surveys of primarily U.S. populations have correlated these markers with plant hosts and have found that the "rice-strain" is preferentially found on turf grasses (e.g., Bermuda grass) and pasture grasses while the "corn-strain" is most common on corn, sorghum, and cotton (reviewed in Nagoshi and Meagher 2004b). Fall armyworm has a large host range, with 186 host plant species from 42 different families recorded to date (Casmuz et al 2010), only a small fraction of which has been linked with a host strain.…”
mentioning
confidence: 99%
“…However, host plant use of this species is wider; the corn strain from the United States to northern South America also has been reported in sorghum and cotton, whereas the rice strain uses pasture grasses as well as rice (Prowell et al 2004, Murúa et al 2008, Vélez-Arango et al 2008. These two strains are identical morphologically but differ in their genetics at several markers at the nuclear and mitochondrial level, including esterase loci and restriction fragment length polymorphisms (Pashley 1986;Levy et al 2002;Nagoshi andMeagher 2003, 2004;Prowell et al 2004).…”
mentioning
confidence: 99%